Relationship between Nano-Entrepreneurship and Employees’ Work-Life Balance in a Local Government Unit in the Philippines - Eric John R Cunanan; Christian L Delos Santos; Jaycee B Esguerra; Jesus P Briones; Marmelo V Abante (Research Synergy Foundation, 2025)
The impact of nano-entrepreneurship on work-life balance differs based on the demands of the dual roles of employees in their entrepreneurship and office employment activities. This study assessed nano-entrepreneurship engagement and employees’ work-life balance in a Local Government Unit (LGU) in the Philippines. The study employed a descriptive-quantitative research design using a researcher-structured questionnaire to collect data from 110 nano-entrepreneurship employees of the subject LGU. Data analyses included frequency, percentage, weighted mean, and regression analyses. This study provides empirical evidence that nano-entrepreneurship engagement of employees in the subject LGU is adequate and manageable in terms of balancing work, personal, and professional activities. Moreover, the work-life balance of nano-entrepreneur employees considering the duality of their roles was found to be acceptable and satisfying; however, it has no significant relationship with nano-entrepreneur engagement. The study also disclosed that although employees believe in the advantages of nano-entrepreneurship, they face certain challenges that may not allow them to pursue such opportunities efficiently. Finally, strategies fostering a supportive culture that encourages psychological safety and autonomy were proposed by the researchers to enhance the well-being and productivity of nano-entrepreneur employees while balancing government responsibilities with their entrepreneurial ventures. This study is essential for an organization, whether public or private, in fostering a supportive culture that enhances employees’ financial stability, job satisfaction, and work-life balance through entrepreneurship.